The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/cid/ciab338
|View full text |Cite
|
Sign up to set email alerts
|

Late Conditions Diagnosed 1–4 Months Following an Initial Coronavirus Disease 2019 (COVID-19) Encounter: A Matched-Cohort Study Using Inpatient and Outpatient Administrative Data—United States, 1 March–30 June 2020

Abstract: Background Late sequelae of COVID-19 have been reported; however, few studies have investigated the time-course or incidence of late new COVID-19-related health conditions (post-COVID conditions) after COVID-19 diagnosis. Studies distinguishing post-COVID conditions from late conditions caused by other etiologies are lacking. Using data from a large administrative all-payer database, we assessed the type, association, and timing of post-COVID conditions following COVID-19 diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 14 publications
5
96
3
1
Order By: Relevance
“… 2 However, little is known about the diagnosis, prevalence, phenotype, or duration of long COVID (also known as post-acute COVID syndrome) in children and young people. 3 The English National Institute for Health and Care Excellence (NICE) defines acute COVID-19 as disease with symptoms that last less than 4 weeks after confirmed infection. Ongoing symptomatic COVID-19 is defined as disease with symptoms lasting 4–12 weeks, and post COVID-19 syndrome as disease with symptoms lasting more than 12 weeks.…”
Section: Introductionmentioning
confidence: 99%
“… 2 However, little is known about the diagnosis, prevalence, phenotype, or duration of long COVID (also known as post-acute COVID syndrome) in children and young people. 3 The English National Institute for Health and Care Excellence (NICE) defines acute COVID-19 as disease with symptoms that last less than 4 weeks after confirmed infection. Ongoing symptomatic COVID-19 is defined as disease with symptoms lasting 4–12 weeks, and post COVID-19 syndrome as disease with symptoms lasting more than 12 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Various organ manifestations of long COVID syndrome have already been described. They range from endocrinological and gastroenterological diseases to interstitial lung diseases and myocarditis [12][13][14][15][16][17][18]. Neuropsychiatric complaints, such as persistent fatigue and anosmia, which are perceived as extremely wearing, have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychiatric complaints, such as persistent fatigue and anosmia, which are perceived as extremely wearing, have also been reported. In a matched cohort analysis of 27,589 inpatients and 46,857 outpatients, long COVID occurred at rates of 7% and 7.7%, respectively [12]. Since these data are based on the collection of new ICD-10 codes after having contracted COVID-19, there is a possibility of underdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that experiencing more than five symptoms during the first week of COVID-19 increased the probability of development of long-COVID by 3.5 times. A propensity matched cohort study [17] matched by age, sex, race, ethnicity, clinical conditions, urbanicity, region and month of hospitalization with non-COVID patients using inpatient and outpatient data showed that late health consequences in 1-4 months following COVID-19 diagnosis could directly be imputed to COVID-19. Of patients, 7.0% and 7.7% experienced post-COVID conditions during 1st-and 4th-month controls, respectively, after the initial COVID-19 inpatient hospitalization.…”
Section: Long-covidmentioning
confidence: 99%